Ni(COD)(DQ): An Air‐Stable 18‐Electron Nickel(0)–Olefin Precatalyst. Issue 19 (18th March 2020) - Tran, Van T.; Li, Zi‐Qi; Apolinar, Omar; Derosa, Joseph; Joannou, Matthew V.; Wisniewski, Steven R.; Eastgate, Martin D.; Engle, Keary M.
Abstract: We report that Ni(COD)(DQ) (COD=1, 5‐cyclooctadiene, DQ=duroquinone), an air‐stable 18‐electron complex originally described by Schrauzer in 1962, is a competent precatalyst for a variety of nickel‐catalyzed synthetic methods from the literature. Due to its apparent stability, use of Ni(COD)(DQ) as a precatalyst allows reactions to be conveniently performed without use of an inert‐atmosphere glovebox, as demonstrated across several case studies. Abstract : Old complex, new tricks : Ni(COD)(DQ) (COD=1, 5‐cyclooctadiene, DQ=duroquinone) is a remarkably stable Ni 0 ‐‐olefin complex first described in the 1960s. Its ability to serve as a precatalyst for a variety of nickel‐catalyzed reactions is demonstrated.